Lecture notes on aquaculture economics and farm management (Cantho university), (faculty of fisheries), Viet nam, july 24-28, 1995 - Agbayani, Renato F. (Can tho university, 1995)
This book included research methodologies on aquaculture production economics, investment ananlysis and aquaculture business management,...